The anti-tumoral potential of the saporin-based uPAR-targeting chimera ATF-SAP - Zuppone, S. (Sci Rep, 2020)
The development of personalized therapies represents an urgent need owing to the high rate of cancer recurrence and systemic toxicity of conventional drugs. So far, targeted toxins have shown promising results as potential therapeutic compounds. Specifically, toxins conjugated to antibodies or fused to growth factors/enzymes have been largely demonstrated to selectively address and kill cancer cells. We investigated the anti-tumor potential of a chimeric recombinant fusion protein formed by the Ribosome Inactivating Protein saporin (SAP) and the amino-terminal fragment (ATF) of the urokinase-type plasminogen activator (uPA), whose receptor has been shown to be over-expressed on the surface of aggressive tumors. ATF-SAP was recombinantly produced by the P. pastoris yeast and its activity was assessed on a panel of bladder and breast cancer cell lines. ATF-SAP resulted to be highly active in vitro, as nano-molar concentrations were sufficient to impair viability on tumor cell lines. In contrast to untargeted toxins, the chimeric fusion protein displayed a significantly improved toxic effect in uPAR-expressing cells, demonstrating that the selective activity was due to the presence of the targeting moiety. Fibroblasts were not sensitive to ATF-SAP despite uPAR expression, indicating that cell-specific receptor-mediated internalization pathway(s) might be considered. The in vivo anti-tumor effect of the chimera was shown in a bladder cancer xenograft model. Current findings indicate ATF-SAP as a suitable anti-tumoral therapeutic option to cope with cancer aggressiveness, as a single treatment or in combination with traditional therapeutic approaches, to appropriately address the intra- and inter- tumor heterogeneity.